Immune off‐target effects of Brentuximab Vedotin in relapsed/refractory Hodgkin Lymphoma. (15th February 2019) - Romano, Alessandra; Parrinello, Nunziatina L.; Chiarenza, Annalisa; Motta, Giovanna; Tibullo, Daniele; Giallongo, Cesarina; La Cava, Piera; Camiolo, Giuseppina; Puglisi, Fabrizio; Palumbo, Giuseppe A.; Di Raimondo, Francesco
Summary: Hodgkin Lymphoma (HL) is associated with deep microenvironment re‐shaping and myeloid dysfunction. Given that only limited data are available regarding the role of Brentuximab Vedotin (BV) as single agent in transplant‐naive relapsed/refractory (R/R) patients and its off‐target effects on immune system, we evaluated the amount of regulatory T‐cells (T‐regs), myeloid‐derived suppressor cells (MDSC) subpopulations, and their functional marker, serum arginase‐1 (s‐Arg‐1), in peripheral blood of 15 consecutive R/R HL patients. After a median of four BV cycles, the overall response rate (complete response + partial response) was 47%, with 4 (27%) complete metabolic remissions. BV reduced the absolute number of three MDSC subtypes and s‐Arg‐1 levels. Patients with baseline s‐Arg‐1 ≥200 ng/ml had inferior progression‐free survival at 36 months compared to those with low s‐Arg‐1. T‐regs dysfunction was recovered by BV: absolute T‐regs count was increased after treatment with BV, independently of metabolic response achieved, with a significant reduction of CD30 + T‐regs. Our data disclose off‐target effects of BV in the microenvironment that could explain its deep and durable clinical efficacy.